Public food forest opportunities and challenges in small municipalities. Issue 1 (15th June 2021) - Coffey, Sarah E.; Munsell, John F.; Hübner, Rico; Friedel, Curtis R.
Abstract: The opportunities and challenges associated with public food forest initiatives in small municipalities are understudied compared with large metropolitan counterparts. Research in small population centers is needed to identify and understand factors affecting the growth of public food forests where resources more commonly available in cities often are lacking. To study these factors, we surveyed mayors in Virginia, United States, serving communities with populations under 25, 000. Out of 176 mayors who received a paper survey through the mail, 68 (39%) responded. Mayors perceived long‐term maintenance as the greatest barrier to public food forests and education, recreation, and spiritual experience as the most desirable benefits. Nearly 70% noted that their town has some form of food production on public land but only one‐fifth include food‐producing trees and shrubs. Most municipalities (78%) do not have food‐producing trees and shrubs land use codes. Summated variables representing mayoral ratings of public support and physical space for food forests in their municipalities were used in a k ‐means cluster analysis to group towns into four types: (a) ambivalent and resource‐poor, (b) optimistic and capable, (c) doubtful and unsupported, and (d) unsure with potential. Each community has unique challenges and opportunities, but mayors stressed that providing sociocultural programs and education rather than food access is the most compelling aspect of a public food forest. Core Ideas: Small municipalities lack policies to support food forests in public spaces. Local leaders view maintenance as the greatest barrier to planting edible, woody perennials. Small municipalities vary in their interest and ability to support food forest initiatives. Emphasizing cultural benefits may be an important for increasing food forests in the United States.